Efficacy of Chinese herbal medicine on poststroke depression in animal models: A systematic review and meta-analysis - Li, Li; Huo, Bixiu; Wang, Yuan; Wang, Yao; Gong, Ying; Zhang, Yun; Liu, Tingting; Sha, Guiming; Zheng, Tianru (Frontiers in Neurology, 2023)
Background Poststroke depression (PSD) is a common complication that can seriously affect patients' functional recovery and quality of life after a stroke. Various side effects have been found to be associated with the pharmacological therapies used for PSD. Studies have shown that Chinese herbal medicine (CHM) can effectively improve PSD-like behavior and neurological function in clinical and animal studies. The efficacy of CHM on PSD in animal models has not been systematically analyzed. Methods The following electronic databases were searched for articles published up to September 2022: PubMed, Web of Science, the Cochrane Library, and Embase. Studies that reported the efficacy of CHM in animals with PSD and were written in English were included. Depression-like behavior and the neurological deficit score were assessed as measures of efficacy. The included studies assessed depression-like behavior using sucrose preference, open-field, forced swimming, and tail suspension tests, as well as body weight. The Review Manager version 5.4 and STATA version 13.1 software packages were used for the meta-analysis. The standardized mean difference (SMD) with 95% confidence intervals was used to assess all the outcomes. Subgroup analyses were performed to explore the sources of heterogeneity. The Egger's test and funnel plots were used to assess the potential publication bias. Sensitivity analyses were used to identify the stability of the results. Results A total of 14 studies, including 12 CHMs involving 442 rats, fulfilled the inclusion criteria for meta-analysis. The pooled results showed that CHM significantly alleviated neurological deficits (−1.72 SMD, −2.47– −0.97) and was efficacious in improving the depression-like behavior of rats in the sucrose preference (2.08 SMD, 1.33–2.84), open-field (2.85 SMD, 1.88–3.83), forced swimming (−1.83 SMD, −2.23−1.44), and tail suspension tests (−1.35 SMD, −1.94−0.76). Conclusion Our results suggest that CHM could significantly improve depression-like behavior and neurological function in animals with PSD. The current results should be interpreted with caution because only animal studies were included.